Current political uses of sport revised: Beyond public diplomacy and sportswashing - Costa, R. (2024)
The successful emergence of the Gulf states as central players in the global sporting ecosystem has revived the intellectual debate on the political and diplomatic use of sport. In the last decade, the amount of research on the topic have radically increase. The old narrative traditions explaining sport diplomacy have recently been joined by a new set of literature about the concept of sportswashing, which questions the place of non-democratic governments in the sporting world. Considering that current approaches are somehow limited to explain the real scope of the situation, this article proposes a new systematization of the political and diplomatic use of sport today, differentiating between practices, actors, and objectives. The aim is to demonstrate how sport as a tool of soft power has transcended the limits of public diplomacy and goes far beyond the simplistic and preconceptual analysis developed by authors who support the concept of sportswashing. The new conceptual framework warns that the politicization of sport is not always positive and shows how some political practices can jeopardies the core values of sport and delegitimize its positive aspect. The results open a new agenda for political science research on a topic that, despite its interest and importance, remains understudied.